Atogepant: Mechanism of action, clinical and translational science - Ramesh Boinpally; Mohamad Shebley; Joel M. Trugman (Wiley, 2024)
Abstract Since the discovery of calcitonin gene‐related peptide (CGRP) in 1982, its integral role in migraine pathophysiology, specifically migraine pain, has been demonstrated through cumulative scientific discoveries that have led to the development and approval of migraine‐specific therapeutics. Today, eight drugs, including monoclonal antibodies and small molecule CGRP receptor antagonists, known as gepants, have received approval for acute or preventive treatment of migraine. The primary mechanism of these drugs is to block CGRP signaling, thus preventing CGRP‐mediated nociception and neurogenic inflammation. Here, we focus on atogepant, a highly potent and selective gepant and the first and only oral medication approved for the preventive treatment of both episodic and chronic migraine in adults. In this article, we summarize the role of CGRP in migraine pathophysiology and the mechanism of action of atogepant. In addition, we provide an overview of atogepant's pharmacology and the key clinical trials and outcomes that have demonstrated the safety and efficacy of atogepant.